1985
DOI: 10.1109/tassp.1985.1164593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of architecture implementation on DFT algorithm performance

Abstract: Five major DFT algorithms were evaluated on seven different computers. The relative performances of these algorithms were related to the architecture of each computer by finding a relationship between the execution time and the instruction counts. The relative performance of these algorithms on other Computers is predicted, based on the knowledge of the computer architecture. On certain implementations, data transfers are more important than floating-point additions and multiplications when comparing DFT algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The reasons why certain algorithms perform better on certain computers were briefly explained in terms of four different instruction categories used. Further research is being conducted on the implementation issues of more FCT algorithms on many modem computers and DSPs by incorporating the correlation coefficients (Mechalic et al 1985) between the different instruction categories and the execution times. n 2 = N < < I ; for (k=1; k<m; k t e = PI/n2; n2=n2> > 1; n4=n2> >2:…”
Section: Discussionmentioning
confidence: 99%
“…The reasons why certain algorithms perform better on certain computers were briefly explained in terms of four different instruction categories used. Further research is being conducted on the implementation issues of more FCT algorithms on many modem computers and DSPs by incorporating the correlation coefficients (Mechalic et al 1985) between the different instruction categories and the execution times. n 2 = N < < I ; for (k=1; k<m; k t e = PI/n2; n2=n2> > 1; n4=n2> >2:…”
Section: Discussionmentioning
confidence: 99%
“…Overheads like data movement, address generation and constants generation often significantly affect the speed of computation, especially in high-level language implementations. In fact, it has been shown that (Mehalic et al 1985) the eficiency of a fast algorithm is strongly affected by the architecture of the target machine. On the other hand, popular algorithms like the WFTA and the FFT required large sets of multiplication constants which are not practical to pre-compute and store as program parameters.…”
Section: Software Realizationmentioning
confidence: 99%
“…The effects of the type of architecture on the performance of the FFT are studied in [3]. Computer architectures are divided into three classes: floating-point processors, data transfer processors and vector processors.…”
Section: Theoretical Performancementioning
confidence: 99%
“…Results obtained by [3] showed that the WFTA performs the best on a vector processor because of its matrix structure. The floating point processor is the least suited for the WFTA because of the large number of data transfers necessary to perform the WFTA The radix-2 FFT algorithm performs the best on the floating-point processor because it have very few data transfers to make.…”
Section: Theoretical Performancementioning
confidence: 99%
See 1 more Smart Citation